Medical Humanities Education and Its Influence on Students' Outcomes in Taiwan: A Systematic Review - Hoang, Bao Lan; Monrouxe, Lynn Valerie; Chen, Kuo-Su; Chang, Shu-Ching; Chiavaroli, Neville; Mauludina, Yosika Septi; Huang, Chien-Da (Frontiers in Medicine, 2022)
Abstract Background: Medical education has emphasized the importance of integrating medical humanities training into the curriculum to benefit medical students’ future practice, featuring in the list of national funding priorities for healthcare education research in Taiwan for many years. However, the extent to which this drive has resulted in medical humanities training, what rationales underpin its’ inclusion, and its’ efficacy is largely unknown. This study aims to address these issues across medical humanities programs within the Taiwanese context. Methods: We conducted a systematic review. Inclusion criteria included studies in English or Mandarin reporting outcomes of medical humanities courses in healthcare education settings in Taiwan between 2000 – 2019. We searched across five electronic databases (PubMed, Embase, ERIC, PsycInfo, Web of Science), following PRISMA guidelines. The Best Evidence Medical Education (BEME) Global Scale and Kirkpatrick Levels are used for identifying the strength of evidence. Results: 17 articles were extracted from the 134 identified. Intrinsic and instrumental rationales for the inclusion of medical humanities education were common, compared with epistemological-based and critical-based approaches. Several positive impacts were identified in relation to participation including modification of attitudes, knowledge, and skills. However, the highest level (i.e. unequivocal) of evidence characterized by effects on students’ behaviors or ongoing interaction with colleagues and patients is lacking. Conclusion: Findings suggest that although medical humanities education is widely implemented in Taiwan, no clear consensus has been reached regarding the rationale for inclusion or how it is localized from Western to Asian contexts. Future research still needs to explore the long-term impact of medical humanities education for medical and nursing students and its impact on patient care.